INFLUENCE OF IMIDACLOPRID ON IOCHEMICAL PARAMETERS IN SOIL ISOLATE ESCHERICHIA COLI - A. A SHETTI; A. G. KULKARNI; R. B. KALIWAL; C. T. SHIVASHARANA; B. B. KALIWAL (International Journal of Pharma and Bio Sciences, 2012)
Imidacloprid (I-[(6-chloro-3-pyridinyl)-methyl]-N-nitro-2-imidazolidinimine), a chloronicotinyl insecticide is used widely to control biting and sucking insects. Present investigation was carried out to analyse the effect of imidacloprid on biochemical parameters like DNA, RNA, protein and glucose in soil isolate Escherichia coli, further the toxic effect of the insecticide on the growth was also studied. The study involving soil isolate Escherichia coli with molar concentrations of 10-3 to 10-7 of imidacloprid insecticide showed that there was an increase in the percent inhibition of DNA, RNA, protein and glucose, the inhibitory effect increased with an increase in the concentration of insecticide proving that the inhibitory effect is dose dependent. Further, imidacloprid inhibited the growth of Escherichia coli when compared to control. The present investigation indicates that imidacloprid reduced the DNA RNA, glucose and protein content which intern effects the growth of the Escherichia coli.